Transfer of Power in India - V P Menon; MENON (V P) (Hyderabad Orient Longman, 1999)
The story of the transfer of power is covered in this book from the outbreak of the Second World War in September 1939 to the beginning of a new phase of Indian history on 15th August 1947. The narrative deals with the August offer of 1940, the Cripps negotiation, the 'Quit India' resolution of 1942, the Simla Conference, the Cabinet Mission, the interim government and the Union Constituent Assembly. The last Viceroy Lord Mountbatten's determined efforts to find a solution acceptable to both the Congress and the Muslim League are described in detail: the 3 June plan, the Indian Independence bill and the birth of two separate dominions completes the story. The book ends with an account of the communal conflagration which followed immediately after partition.
Keywords: British Policy; All Indian Federation; Simla Conference; Cabinet Mission